2014
DOI: 10.1371/journal.pone.0096703
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Induces NLRP-3-Mediated IL-1β Secretion in Neutrophils

Abstract: Background/AimsSerum amyloid A (SAA) is an acute phase reactant with significant immunological activities, including effects on cytokine synthesis and neutrophil chemotaxis. Neutrophils can also release cytokines with proinflammatory properties. IL-1β is a key proinflammatory cytokine, the secretion of which is controlled by inflammasome. We investigated the proinflammatory effects of SAA in vitro in relation to the NLRP3 inflammasome in neutrophils.Methodology/Principal FindingsHuman neutrophils isolated form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…Infection of H37Rv but not its esat-6 deletion mutant induced elevated expression of SAA3 in macrophages and mouse lungs both at mRNA and protein levels and silencing SAA3 in macrophages resulted in reduced IL-1β but not IL-6 production upon Mtb infection, supporting a role for SAA3 in Mtb- induced IL-1β production in tuberculosis infection. This is consistent with the previous reports showing the potential role of SAA3 activated NLRP3 in mature IL-1β production by macrophages in chronic allergic diseases (32) and SAA3 induces transcription and maturation of IL-1β in macrophages (14) and neutrophils (37). This study further extends the role of SAA3 in Mtb -induced IL-1β production, thus suggesting a potential role of SAA3 in both the immune responses against and the pathology of tuberculosis infection at least in part by regulation of IL-1β production by macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Infection of H37Rv but not its esat-6 deletion mutant induced elevated expression of SAA3 in macrophages and mouse lungs both at mRNA and protein levels and silencing SAA3 in macrophages resulted in reduced IL-1β but not IL-6 production upon Mtb infection, supporting a role for SAA3 in Mtb- induced IL-1β production in tuberculosis infection. This is consistent with the previous reports showing the potential role of SAA3 activated NLRP3 in mature IL-1β production by macrophages in chronic allergic diseases (32) and SAA3 induces transcription and maturation of IL-1β in macrophages (14) and neutrophils (37). This study further extends the role of SAA3 in Mtb -induced IL-1β production, thus suggesting a potential role of SAA3 in both the immune responses against and the pathology of tuberculosis infection at least in part by regulation of IL-1β production by macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Other groups have reported that SAA stimulates dendritic cells, macrophages, and neutrophils to secrete IL-1β by activating the NLRP3 inflammasome (8)(9)(10). However, these studies utilized a recombinant SAA protein that has 2 amino acid substitutions (at positions 61 and 72) when compared to native SAA1, and recent evidence suggests that this recombinant form of SAA may exert activities not shared by mouse or human SAA (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…SAA stimulates secretion of IL-1β in human and mouse macrophages, dendritic cells and neutrophils (8)(9)(10). SAA represents a family of proteins with 103-104 amino acids that share high sequence homology that presumably arose from gene duplication.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Recent evidence has indicated that SAA possesses a number of cytokine‐like properties. It has been reported that SAA stimulates the release of mature IL‐1β from neutrophils, mast cells, macrophages and fibroblasts . However, whether or not SAA can induce IL‐1β production in keratinocytes remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%